Migrating from integrated library systems to library services platforms - Grammenis, Efstratios; Mourikis, Antonios (Qualitative and Quantitative Methods in Libraries, 2020)
The present paper is based on a master thesis work that was carried out in the Linnaeus University (Sweden) and is an exploratory qualitative study in academic libraries regarding the transition from the integrated library systems to the next generation integrated library systems or library services platforms and the potential implications in their internal workflows. In our study we explored the phenomenon in the globe studying the international literature and by conducting two methods of the qualitative approach that of semi-structured interviews and observation we identified that not only there are important implications on libraries’ workflows but also that new ones have been created. The results of our study are presented in the paper along with a comparison between the Greek situation and the international one.